Intra- and Interreligious Dialogue in Flemish (Belgian) Secondary Education as a Tool to Prevent Radicalisation - Lafrarchi, Naïma (Religions, 2021)
The attacks in Paris (2015) and Brussels (2016) led to the development of an Action Plan against radicalisation wherein Islamic religious teachers are expected to contribute actively to de-radicalisation processes and counter-discourse. To this end, Flemish teacher training university colleges have rapidly established new ‘Islamic religious education’ (IRE) teacher training programs. Additionally, the Minister of Education made interconvictional dialogue lessons mandatory in compulsory education. These lessons aim to stimulate, strengthen and reinforce the dialogue between pupils of different belief system backgrounds. Thus, the interconvictional competences are seen as a means to prevent radicalisation and polarisation. This article draws an overview of IRE development since 2015 until now regarding the policy incentives concerning the Flemish IRE, taking into account the concept of separation of Church and State. Furthermore, we scrutinise the existing IRE teacher training curricula with regard to the formulated interconvictional competence elements, as these are seen as one of the remedies for radicalisation and polarisation. We observe a clear relationship between the dramatic events and the implementation of new Islamic religious education programs and partnerships. An increasing number of ‘interconvictional’ references are observed in the Islam-related courses that are included in IRE teacher training programs. Further in-depth field research is needed to map the IRE teaching practices and experiences regarding the expectations formulated by policy makers.